Potassium translocation by the Na+/K+ pump is voltage insensitive. - Bahinski, A (1988)
The voltage dependence of steady and transient changes in Na+/K+ pump current, in response to step changes in membrane potential, was investigated in guinea pig ventricular myocytes voltage clamped and internally dialyzed under experimental conditions designed to support four separate modes of Na+/K+ pump activity. Voltage jumps elicited transient pump currents when the pump cycle was running forward or backward, or when pumps were limited to Na+ translocation, but not when they were made to carry out K+/K+ exchange. This result indicates that K+ translocation involves no net charge movement across the membrane field and is therefore voltage insensitive. The transient pump currents seen during Na+/K+ transport demonstrate that both forward and reverse pump cycles are rate limited not by the voltage-dependent step but by a voltage-independent step, probably K+ translocation. These findings severely constrain kinetic models of Na+/K+ pump activity.